2023
DOI: 10.1002/adtp.202200305
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Lipid Nanoparticles can Deliver Messenger RNA Payloads and Improve their Endosomal Escape

Abstract: Even though lipid nanoparticles (LNPs) can deliver messenger RNA (mRNA) payloads into cells, their efficiency is often limited by endosomal trapping which prevents RNA payloads from acting therapeutically. Improving the percentage of RNA LNPs that can escape from endosomes and enter the cytoplasm is therefore an area of active research interest that could lead to improved safety profiles and reduced manufacturing costs of mRNA drugs. Here, tannic acid mRNA LNPs [TA(+) mRNA LNPs] are reported as an effective de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To begin our study, we formulated and characterized 4 mRNA LNP formulations inspired by the Moderna and Pfizer/BioNTech COVID-19 LNP formulations, as well as by our previous work on tannic acid (TA) mRNA LNPs. Briefly, ethanol phases containing specified molar ratios of ionizable lipid (either Moderna’s SM-102 or Pfizer/BioNTech’s ALC-0315), cholesterol, , phospholipid (DOPE, which was used because we have previously observed it to improve the efficacy of LNPs relative to DSPC), polyethylene glycol, and TA (where relevant) were microfluidically mixed with an aqueous phase containing mRNA encoding for the reporter gene firefly luciferase (FLuc) (Figure a–c). The size, charge, and encapsulation efficiency were reproducible for each formulation, with sizes ranging from 146 to 246 nm, zeta potentials ranging from −5.3 to 0.8 mV, and encapsulation efficiencies ranging from 62 to 80%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To begin our study, we formulated and characterized 4 mRNA LNP formulations inspired by the Moderna and Pfizer/BioNTech COVID-19 LNP formulations, as well as by our previous work on tannic acid (TA) mRNA LNPs. Briefly, ethanol phases containing specified molar ratios of ionizable lipid (either Moderna’s SM-102 or Pfizer/BioNTech’s ALC-0315), cholesterol, , phospholipid (DOPE, which was used because we have previously observed it to improve the efficacy of LNPs relative to DSPC), polyethylene glycol, and TA (where relevant) were microfluidically mixed with an aqueous phase containing mRNA encoding for the reporter gene firefly luciferase (FLuc) (Figure a–c). The size, charge, and encapsulation efficiency were reproducible for each formulation, with sizes ranging from 146 to 246 nm, zeta potentials ranging from −5.3 to 0.8 mV, and encapsulation efficiencies ranging from 62 to 80%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Toward our goal of establishing ATP co-delivery as a uniform strategy to improve the activity of multiple types of mRNA LNPs, we began our study by formulating four mRNA LNPs of various chemistries that contained ATP [deemed ATP­(+)]; four mRNA LNP analogs that did not contain ATP [deemed ATP(−)] were also prepared. Briefly, this was accomplished by microfluidically mixing an aqueous phase containing mRNA (and optionally ATP) with an ethanol phase containing different types of ionizable lipids (either Moderna’s SM-102 or Pfizer/BioNTech’s ALC-0315, to maximize translational relevance), , the phospholipid DOPE (which was used because we have previously observed it to improve the efficacy of LNPs relative to DSPC), , cholesterol, , lipid anchored polyethylene glycol, and tannic acid (TA, a biomolecule that can be added to LNPs to enhance mRNA delivery to target cells) ,, (Figure a–c). The size, charge, and encapsulation efficiency for each mRNA LNP was reproducible, with sizes ranging from ∼132 to ∼415 nm (Figure d), zeta potentials ranging from ∼−0.5 to ∼4.7 mV (Figure e), FLuc mRNA encapsulation efficiencies of LNPs ranging from ∼64% to ∼85% (Figure f), and ATP encapsulation efficiencies ranging from ∼18% to ∼29% (Figure g).…”
Section: Resultsmentioning
confidence: 99%
“…And fourth, calcein distribution throughout cells treated with 1-ATP­(+) formulations was greater than that observed in cells treated with their corresponding 1-ATP­(−) formulations, while calcein distribution in cells treated with the 4-ATP­(+) formulations was similar to what was observed in cells treated with the 4-ATP­(−) formulation (Figure ). While it may be complex to pinpoint the exact reason behind this, one possible explanation is that 4-ATP­(+) and 4-ATP­(−) LNPs contain TA, while 1-ATP­(+) and 1-ATP­(−) LNPs do not, highlighting that utilizing different chemistries in LNPs can possibly be used as a tool to manipulate cellular uptake pathways including endosomal escape. Notably, mixing TA and ATP does not appear to result in covalent bond formation, suggesting that each molecule may play a role in improving the overall activity of mRNA LNPs (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, hexagonal structures of helper lipids such as DOPE (inverted-cone lipids) could facilitate membrane fusion and promote endosomal escape of LNPs, compared to bilayer structures of DSPC (cone lipids) . In additional examples, adding additional excipients like tannic acid (TA) could also facilitate the endosomal escape of the LNPs in MDCK cells . They also reported that hypoxia decreased the efficacy of LNPs due to differences in ATP in normoxic vs hypoxic cells rather than in how cells respond to mRNA LNPs .…”
Section: Therapeutic Nucleic Acid Delivery Strategiesmentioning
confidence: 99%
“…135 In additional examples, adding additional excipients like tannic acid (TA) could also facilitate the endosomal escape of the LNPs in MDCK cells. 136 They also reported that hypoxia decreased the efficacy of LNPs due to differences in ATP in normoxic vs hypoxic cells rather than in how cells respond to mRNA LNPs. 137 A follow up work is to develop a unified strategy by codelivering mRNA and ATP inside LNPs, which may have the potential for treating hypoxic diseases.…”
Section: Viral Vectorsmentioning
confidence: 99%